2016
DOI: 10.1159/000442002
|View full text |Cite
|
Sign up to set email alerts
|

The New Generation Mini-PCNL System - Monitoring and Controlling of Renal Pelvic Pressure by Suctioning Device for Efficient and Safe PCNL in Managing Renal Staghorn Calculi

Abstract: Introduction: In order to better control renal pelvic pressure (RPP), reduce surgical complications and increase operative efficacy of minimally invasive percutaneous nephrolithotomy (MPCNL), we designed an MPCNL with intelligent monitoring and control of RPP and sought to explore its clinical efficacy and characteristics. Subject and Methods: This study included 60 patients with renal staghorn calculi. A 5F ureteral catheter was connected to an invasive blood pressure monitor for monitoring and control of RPP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…For reducing the renal pelvic pressure, there are many methods such as adding isoproterenol to the surgical perfusion solution using a dual-channel continuousflow URS and a traditional UAS for F-URS (25-28). In addition, studies have shown that vacuum suctioning can reduce renal pelvic pressure efficiently and significantly increase the safety and efficacy of minimally invasive suctioning PCNL (29)(30)(31). Consistent with this, another study showed that a ureteroscopy featuring a vacuum suction system is effective and safe for treating upper urinary tract calculi (32).…”
Section: Discussionmentioning
confidence: 77%
“…For reducing the renal pelvic pressure, there are many methods such as adding isoproterenol to the surgical perfusion solution using a dual-channel continuousflow URS and a traditional UAS for F-URS (25-28). In addition, studies have shown that vacuum suctioning can reduce renal pelvic pressure efficiently and significantly increase the safety and efficacy of minimally invasive suctioning PCNL (29)(30)(31). Consistent with this, another study showed that a ureteroscopy featuring a vacuum suction system is effective and safe for treating upper urinary tract calculi (32).…”
Section: Discussionmentioning
confidence: 77%
“…Yang et al. [ 11 ] demonstrated the efficient use of mini-PCNL with suctioning system to control renal pelvic pressure, reduce complications, and improve operative time in renal staghorn calculi.…”
Section: Discussionmentioning
confidence: 99%
“…The prolonged course of disease and the location of stones at the junction of the renal pelvis can aggravate urinary tract obstruction and hydronephrosis, aggravate renal parenchyma injury, and further induce renal atrophy. Under the condition of high-pressure perfusion during PCNL, the structure of nephrons gradually changes with increased pressure, with diffuse exfoliation and flattening of calyceal urothelium, submucosal edema and congestion, and vacuolation of renal tubules, which further impair renal function [ 26 , 27 ]. The present study found that intraoperative perfusion pressure >30 mmHg was an independent risk factor for renal atrophy in PCNL, which suggests that strict control of intraoperative perfusion pressure is an important measure to avoid intraoperative renal injury and postoperative renal atrophy.…”
Section: Discussionmentioning
confidence: 99%